CONTRIBUIÇÕES PARA O PLANEJAMENTO DE APOSENTADORIA DE SERVIDORES PÚBLICOS EM UMA INSTITUIÇÃO FEDERAL DE ENSINO - Girelli, Dereck Bruno (2022)
Introduction: The reforms of the public pension system, the macro and microeconomic situation, financial literacy, the variation in cognitive capacity and possible effects with advancing age are some arguments that suggest a reflection on retirement planning from the beginning of the professional career. A bibliometric quantitative approach through systematic review was used as a methodology for the construction of the practical reference. Preparing for retirement is a complex activity, since the elements for decision making related to investments in social security are diversified and surrounded by risks. Although the transformations of retirement systems placed an active responsibility on the worker for retirement planning, the employer still exerts influence on the planning capacity of its employees, considering the procrastination in the execution of these plans. The problem verified is the inexistence of permanent institutional actions towards the retirement planning of the servers in the Federal Institute of Espírito Santo. In this way, the research question was: how to contribute to the retirement planning of public servants in a Federal Teaching Institution? Faced with this questioning, the objective of this research was to seek ways of contributing to the retirement planning of career civil servants of Federal Education Institutions. The Brazilian legal system advocates the creation of Retirement Preparation Programs, which have actions related to workers' finances. As for the methodological procedure for the development of the technical product, an approach of document analysis was used, in which Institutes belonging to the Federal Network of Professional, Scientific and Technological Education and Federal Public Universities that already had PPA in execution for their servers and benchmarking of these products in relation to the retirement preparation program generated with the preliminary results of the systematic review. The results of the systematic review pointed out the motivations for carrying out retirement planning, while the documentary approach showed a reduced number of institutions that carry out this training action. In this way, as a technical product, it was intended to build a program of preparation for retirement, considering what is practiced in other organizations with professional careers similar to Ifes, which can guide actions to be instituted by the Federal Institute of Espírito Santo as a way to train its staff for this important topic.